Biosynthesis and in vitro enzymatic synthesis of the isoleucine conjugate of 12-oxo-phytodienoic acid from the isoleucine conjugate of α-linolenic acid. Issue 6 (1st April 2018) - Uchiyama, Akira; Yaguchi, Takaomi; Nakagawa, Hiroyuki; Sasaki, Kento; Kuwata, Naoshige; Matsuura, Hideyuki; Takahashi, Kosaku
Graphical abstract: Abstract: The isoleucine conjugate of 12-oxo-phytodienoic acid (OPDA-Ile), a new member of the jasmonate family, was recently identified in Arabidopsis thaliana and might be a signaling molecule in plants. However, the biosynthesis and function of OPDA-Ile remains elusive. This study reports an in vitro enzymatic method for synthesizing OPDA-Ile, which is catalyzed by reactions of lipoxygenase (LOX), allene oxide synthase (AOS), and allene oxide cyclase (AOC) using isoleucine conjugates of α -linolenic acid (LA-Ile) as the substrate. A. thaliana fed LA-Ile exhibited a marked increase in the OPDA-Ile concentration. LA-Ile was also detected in A. thaliana. Furthermore, stable isotope labelled LA-Ile was incorporated into OPDA-Ile. Thus, OPDA-Ile is biosynthesized via the cyclization of LA-Ile in A. thaliana.